A Study About The Effect of Type-II Collagen on Balance Performance in Women With Knee Osteoarthritis - Taşkın, Cengiz; TAŞKIN, Ali Kemal; TÜMKAYA, Ümmühan; YAMAKOĞLU, Ercan; DELİHACIOĞLU, Cevdet Can and YILMAZ, Mehmet (Progress in Nutrition, 2022)
In this study, the effect of hydrolyzed type-II collagen supplementation on Y balance performance investigated in patients with stage 2-3 osteoarthritis according to Kellgren Lawrence radiological staging. A total of 20 female patients that consists of 10 experimental groups with a average age of 38.7 ± 2.70 and 10 control groups with a average age of 38.3 ± 1.99 were included in the study. Tthe experimental group patients received paracetamol treatment with 1500 mg/day for three months orally hydrolyzed type-II collagen treatment on an empty stomach 10 g/day in the morning. The patients in the control group received only 1500 mg/day paracetamol treatment for three months. As a result of the statistical analysis that is performed at the end of the study, it is found that there are statistically significant differences in the Y balance’s pre-test and post-test performance values of the experimental group (p <0.05). However, there is no significant difference in the pre-test and post-test performance values of the control group (p> 0.05). As a result, it can be said that type-II collagen supplementation, which is one of the building blocks of joint cartilage in the body, can provide positive effects on the balance performance of female patients with knee osteoarthritis.